Granulomatose mit Polyangiitis - Kerstein, Anja; Holl-Ulrich, Konstanze; Müller, Antje; Riemekasten, Gabriela; Lamprecht, Peter (DMW - Deutsche Medizinische Wochenschrift, 2017)
Granulomatosis with polyangiitis (GPA) is a potentially life-threatening, rare disease. The etiology is unknown. GPA is histomorphologically characterized by extravascular necrotizing granulomatous inflammation and a systemic necrotizing vasculitis of small to medium-sized vessels. Clinically, a pulmonary-renal syndrome with pulmonary infiltrates, alveolar hemorrhage and a rapidly progressive glomerulonephritis is seen in about 80% of the cases with generalized disease. GPA is associated with proteinase 3-specific anti-neutrophil cytoplasmic autoantibodies (PR3-ANCA). Treatment is guided by severity of organ involvement and disease activity. Cytostatic immunosuppressants or the monoclonal anti-CD20 antibody rituximab are applied.
Keywords: Granulomatose mit Polyangitiis; ANCA; Proteinase 3; Nekrose; Entzündung